PENYULUHAN TENTANG COVID-19 DENGAN PEMANFAATAN MEDIA POSTER PADA MASYARAKAT DI DESA MANGUNREJO - Ratnawati, Riska; D, Afifah Nur; Andini, Anggie Nur; Indrasena, Bangkit (Universitas Respati Yogyakarta, 2021)
The high incidence of the spread of the covid-19 virus has caused very high fear for the entire world community, especially those of us who live in Indonesia, the Corona Virus, which we know as Covid-19, was first discovered in Wuhan China, at the end of December 2019. Covid disease -19 is most contagious when the person suffering from it has symptoms, although the spread may occur before symptoms appear (Rothan, 2020). Covid-19 cases in Indonesia have increased every day based on data obtained from Deti Mega Purnamasari through kompas.com until April 15, 2020, there were 5,136 positive cases of covid-19. The positive number of Covid-19 in East Java, especially Magetan Regency, continues to increase. Magetan Regency is in 30th place compared to other districts / cities in East Java with an upward trend in the epidemic. Almost all areas in Magetan Regency have contracted this virus, one of which is Desa Mangunrejo, Kawedanan District, Magetan Regency. The purpose of this community service activity is to provide knowledge about how to prevent the spread of the covid-19 virus for the general public, especially in Mangunrejo Village. The method of implementing this community service is providing health education about symptoms, ways of transmission and prevention of Covid-19. The result increases the knowledge of the people of Mangunrejo Village, Magetan Regency.Â Keywords: Counseling, Covid-19, Poster